'Uncle Tom was there, in crockery': Material Culture and a Victorian Working-class Childhood. (1st September 2013) - Crewe, V A; Hadley, D M
Abstract : British archaeologists have long recognised the potential for the archaeology of working-class neighbourhoods to illuminate communities that typically left few direct traces of their own in the written record. They have also emphasised that the diversity of material culture from such sites provides alternative perspectives to the textual evidence, which is often moralising and condemnatory. Drawing on a case-study from Sheffield in Yorkshire, England, this paper explores what material culture can reveal about working-class childhoods. It argues that childhood was depicted and experienced at the intersections of the chapel, mine and pub, and that competing conceptions of childhood and family were pivotal to the struggle for working-class identity.